Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Aset Perusahaan Asuransi Syariah di Indonesia Tahun 2014 - Cholifatulaini, Sofiyana Elya; , Drs. Triyono, M.Si; , Drs.Harun.MH (2016)
Assets are used for operations of the company. The larger the assets greater operational results produced by the company. The increase in assets followed by an increase in operating results which will further add credence outside parties against the company. Healthy asset growth is considered as one of the foundations of the company's success. Among the internal factors that affect the growth rate of the insurance company's assets include investments, premiums and claims. This study aimed to test whether the variable Investments, Premiums and Claims affect the growth of assets in the Company's Sharia Insurance in Indonesia with the object of research is Life Insurance Company Syariah Life Insurance Company which has Sharia Unit, the General Insurance Company of Sharia, and General Insurance Company has Syariah units using secondary data. Data analysis technique used is the analysis method OLS (Ordinary Least Square) using data between the space (cross section). The results of the t test showed that the variable Investment positive and significant impact on the Growth Assets, while variable premiums and claims does not significantly influence the growth of assets in Islamic Insurance Company in Indonesia. And the result of simultaneous F test shows that the variable Investments, Premiums and Claims jointly significant effect on growth of assets in Islamic Insurance Companies in Indonesia in 2014.